Sparring and Neurological Function in Professional Boxers - Stiller, John W. (Frontiers Media S.A., 2014)
Despite increased interest regarding the potentially long-term negative impact of chronic traumatic brain injury, limited research has been conducted regarding such injuries and neurological outcomes in real world settings. To increase understanding regarding the relationship between sparring (e.g., training under the tutelage of an experienced boxing coach for the purpose of improving skills and/or fitness) and neurological functioning, professional boxers (n = 237) who competed in Maryland between 2003 and 2008 completed measures regarding sparring exposure (Cumulative Sparring Index, CSI) and performance on tests of cognition (Symbol Digit Modalities Test, SDMT) and balance (Sharpened Romberg Test, SRT). Measures were completed prior to boxing matches. Higher scores on the CSI (increased sparring exposure) were associated with poorer performance on both tests of cognition (SDMT) and balance (SRT). A threshold effect was noted regarding performance on the SDMT, with those reporting CSI values greater than about 150 experiencing a decline in cognition. A history of frequent and/or intense sparring may pose a significant risk for developing boxing associated neurological sequelae. Implementing administration of clinically meaningful tests before bouts, such as the CSI, SDMT, and/or the SRT, as well as documentation of results into the boxer’s physicals or medical profiles may be an important step for improving boxing safety.